2016
DOI: 10.1371/journal.pone.0151184
|View full text |Cite
|
Sign up to set email alerts
|

The Formulation of Bacteriophage in a Semi Solid Preparation for Control of Propionibacterium acnes Growth

Abstract: AimsTo isolate and characterise phage which could lyse P. acnes and to formulate the phage into a delivery form for potential application in topical treatment of acne infection.Methods and ResultsUsing standard phage isolation techniques, ten phage capable of lysing P. acnes were isolated from human skin microflora. Their genomes showed high homology to previously reported P. acnes phage. These phage were formulated into cetomacrogol cream aqueous at a concentration of 2.5x108 PFU per gram, and shown to lyse u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 47 publications
(63 reference statements)
5
60
0
2
Order By: Relevance
“…Topical probiotics may also include C. acnes bacteriophages, which are viruses that can lyse host bacteria. Two studies showed that some C. acnes bacteriophages lyse only acne‐associated and uncorrelated (potentially pathogenic) phylotypes, but are often ineffective against phylotypes associated with healthy skin . This potential combination of healthy‐skin‐associated C. acnes together with bacteriophages that target other C. acnes could potentially allow for highly specific strain replacement (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Topical probiotics may also include C. acnes bacteriophages, which are viruses that can lyse host bacteria. Two studies showed that some C. acnes bacteriophages lyse only acne‐associated and uncorrelated (potentially pathogenic) phylotypes, but are often ineffective against phylotypes associated with healthy skin . This potential combination of healthy‐skin‐associated C. acnes together with bacteriophages that target other C. acnes could potentially allow for highly specific strain replacement (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…For the creams, ointments and paste, P. acnes phage PAC1 was used . Phage were mixed by gradual geometric dilution to the creams, ointments and pastes to a final concentration of 2.5 × 10 8 PFU/g.…”
Section: Methodsmentioning
confidence: 99%
“…To this end, we have used various models for testing the effectiveness of these dosage forms. The first involves Propionibacterium acnes as the test bacteria (the causative agent of acne vulgaris), and our previously published bacteriophage PAC1, which is lytic against P. acnes . These phage were formulated into a range of hydrophilic bases of diverse ionic nature, as well as more hydrophobic and more occlusive bases, to test their efficacy as vehicles in phage therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Further support for a role for C. acnes is that acne prevalence decreases with increasing age, likely as a result of decreased sebum production with age, but the change in sebum secretion may be linked to changes in microbiome composition. Although there is promising evidence for the use of lytic formulations with bacteriophages for reducing C. acnes growth in vitro , substantial future work will be required to prove the utility of bacteriophage for treating human acne …”
Section: Acne and Skin Bacteriamentioning
confidence: 99%
“…Although there is promising evidence for the use of lytic formulations with bacteriophages for reducing C. acnes growth in vitro, substantial future work will be required to prove the utility of bacteriophage for treating human acne. 39,40 While much evidence exists supporting the role of C. acnes in acne, the topic remains controversial. C. acnes is also considered a host-beneficial microbe.…”
Section: Acne and Skin Bacteriamentioning
confidence: 99%